Measuring the Role of Leadership Style and Decision Making in Creating Performance (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to investigate the influence of leadership style and decision-making on the performance of employees at Dealer Honda Semarang Center. Employing a quantitative methodology and survey approach, the study selected participants through proportional random sampling, resulting in a sample size of 71 responses. Data analysis was conducted using SPSS version 26, employing multiple regression, t-test, and F-test techniques. The findings revealed positive regression coefficients for both decision-making (X2) and leadership style (X1) variables in relation to performance (Y), indicating a beneficial impact on performance. Specifically, leadership style (X1) demonstrated a partial influence on performance, while decision-making (X2) showed a significant impact. The study concludes that both leadership style and decision-making variables collectively account for 43.5% of the variation in performance, with the remaining percentage attributed to unexplored factors.
Keywords: Leadership Style; Decision Making; Performance Employees; Dealer Honda Semarang Center